Hierarchical graphene/CdS/Ag2S sandwiched nanofilms for photoelectrochemical water splitting. (10th September 2015) - Wang, Bo; Liu, Zhifeng; Han, Jianhua; Hong, Tiantian; Zhang, Jing; Li, Yajun; Cui, Ting
Graphical abstract: Abstract: In this work, an efficient photocatalytic material was prepared directly on Indium tin oxide (ITO) glass substrates by fabricating CdS and Ag2 S onto graphene via a facile, room-temperature and low-cost successive ionic layer adsorption and reaction (SILAR) for photoelectrochemical (PEC) water splitting. The hierarchical graphene/CdS/Ag2 S (G/CdS/Ag2 S) sandwiched semiconducting materials were characterized, and found to have an excellent effect in the light absorption. The photocurrent density of the G/CdS/Ag2 S nanofilms for photoelectrochemical water splitting was measured to be up to 5.18 mA/cm 2, which could be ascribed to the followings: (i) a higher efficiency of light-harvesting because of Ag2 S coupling with CdS that could broaden the absorbing solar spectrum and enhance the light utilization efficiency; (ii) a stepwise structure of band-edge levels in the G/CdS/Ag2 S electrode was constructed which was attributed to Fermilevel alignment between CdS and Ag2 S; (iii) An electron accelerator (graphene) was used in the CdS/Ag2 S materials to get better electron-injecting efficiency.